Guaiane-type sesquiterpenoids from Cinnamomum migao H. W. Li: And their anti-inflammatory activities. (October 2021) - Muhammad, Ishaq; Luo, Wei; Shoaib, Rana Muhammad; Li, Guang-li; Shams ul Hassan, Syed; Yang, Zhi-hua; Xiao, Xue; Tu, Guo-li; Yan, Shi-Kai; Ma, Xian-peng; Jin, Hui-Zi
Abstract: The phytochemical assessment of Cinnamomum migao H. W. Li fruits illustrated the isolation and identification of ten undescribed guaiane-type sesquiterpenoids "miganoids A−J″ and one undescribed sesquiterpene "7(S)-(hydroxypropanyl)-3-methyl-2-(4-oxopentyl) cyclohex-2-en-1-one". The extensive analysis of HRESIMS, 1D NMR, 2D NMR, experimental circular dichroism (ECD), and calculated (ECD) analysis entirely corroborated the configuration and confirmation of these isolated compounds. Moreover, the anti-inflammatory properties of the reported compounds were established by determining the LPS induced nitric oxide production. In the current study, miganoid C is testified the most active compound with about 89% NO inhibition. Additionally, miganoids C, E, and G also exhibited moderate inhibitory effects against the pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6). The IC50 values for miganoid C and miganoid G were determined as 19.4 and 14.5 μΜ against TNF-α mRNA, respectively. Graphical abstract: Image 1 Highlights: Ten undescribed guaiane-type sesquiterpenoids and one undescribed sesquiterpenoid were isolated from Cinnamomum migao H. W. Li. These undescribed compounds were named as "miganoids A−J″ and "7 (S)-(hydroxypropanyl)-3-methyl-2-(4-oxopentyl) cyclohex-2-en-1-one". Their absolute configurations were determined by NMR analyses and CD data. All the isolated compounds were assessed for their anti-inflammatory activities.